2021
DOI: 10.1007/s00484-021-02167-0
|View full text |Cite
|
Sign up to set email alerts
|

Negative relationship between dry matter intake and the temperature-humidity index with increasing heat stress in cattle: a global meta-analysis

Abstract: Changes in frequency and severity of heat waves due to climate change pose a considerable challenge to livestock production systems. Although it is well known that heat stress reduces feed intake in cattle, effects of heat stress vary between animal genotypes and climatic conditions and are context specific. To derive a generic global prediction that accounts for the effects of heat stress across genotypes, management and environments, we conducted a systematic literature review and a meta-analysis to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 53 publications
(76 reference statements)
0
17
0
Order By: Relevance
“…The periods with the highest risk of heat stress to cattle in the state are from October to December, in which the THI average exceeds 73.07, reaching 75.47 in places like Hidrolândia, located just 35.9 km south of Goiânia. Locations with high THI values may present reduced feeding and increased water intake by cattle, consequently reducing milk production and changing solid composition 54,55 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The periods with the highest risk of heat stress to cattle in the state are from October to December, in which the THI average exceeds 73.07, reaching 75.47 in places like Hidrolândia, located just 35.9 km south of Goiânia. Locations with high THI values may present reduced feeding and increased water intake by cattle, consequently reducing milk production and changing solid composition 54,55 …”
Section: Resultsmentioning
confidence: 99%
“…Locations with high THI values may present reduced feeding and increased water intake by cattle, consequently reducing milk production and changing solid composition. 54,55 Among the eight main localities in the region, only Sinop (MT) and Cuiabá (MT) did not present 'critical alerts' during the spring/summer. The municipality of Corumbá is the second location with the largest cattle herd in the country (1 775 391 cattle heads), however, it presented a 'critical alert' during the summer, mainly during November and December (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The equation developed by the National Research Center in 1971 [ 20 , 22 ], THI = (1.8 × AT avg + 32) − [(0.55 − 0.0055 × RH avg ) × (1.8 × AT avg − 26) where T = dry bulb temperature (°C) and RH avg is daily mean relative humidity (%) is regarded as the most appropriate and is routinely used in heat stress studies conducted in several climates [ 23 , 24 ]. The strong relationship between THI and a variety of variables, including heart rate, respiration rate, rectal and vaginal temperature, and dry matter intake (DMI), has been highlighted in the literature [ 25 , 26 , 27 ] ( Figure 2 ).…”
Section: Impact Of Heat Stress On Udder Health Livestock Production A...mentioning
confidence: 99%
“…The relationship between THI and milk yield may be assessed using a reference equation provided by Berry et al (1964) [ 31 ]. According to the authors the: Decline in milk yield (kg/d) = − 1.075 – 1.736 × NL + 0.02474 × NL × THI where NL is the usual daily milk production (kilograms per day) measured between the optimal temperature level for cattle, considered to range between −13 °C −/+ 25 °C [ 27 , 29 , 30 ] and THI is the daily mean temperature–humidity index. Using this equation, it is observable that the daily milk yield (kilograms per day) decreases as the temperature–humidity index increases, especially for higher-productive cows.…”
Section: Impact Of Heat Stress On Udder Health Livestock Production A...mentioning
confidence: 99%
“…Among the greatest barriers to feedlot production in chronically heat-stressed livestock is reduced feed intake [ 49 , 50 ]. Indeed, high THI has a strong inverse correlation with dry matter intake [ 51 ], which predictably reduces the rate and efficiency of weight gain and if sustained can ultimately affect the animal’s health and well-being [ 9 , 52 , 53 ]. A recent study of heat-stressed feedlot wethers found that they had less fat-free lean tissue relative to their total bodyweight [ 54 ].…”
Section: The Impact Of Heat Stress In Livestockmentioning
confidence: 99%